Akurasi Skor Alvarado pada Kasus Apendisitis - Gabriella H. Z. P. Siregar; Angelica M. J. Wagiu; Harsali F. Lampus (Universitas Sam Ratulangi, 2023)
Abstract: The Alvarado score is the first scoring system developed and the most popular used to diagnose appendicitis, with claims to have advantages, namely high diagnostic accuracy, simple and effective. However, in several studies Alvarado's scores were found to be inaccurate and biased toward certain races, genders, and ages. Therefore, many new scoring systems have emerged to determine a more accurate diagnosis of appendicitis. This study aimed to determine the accuracy of the Alvarado score in cases of appendicitis. This was a literature review study using database of the Clinicalkey, Pubmed and Google Scholar and the PICOS framework selection criteria with the keywords 'accuracy' AND ‘alvarado score’ AND 'appendicitis' AND ‘Asia’ OR ‘Indonesia. The results showed that there was no significant difference in score accuracy found between age groups, but Alvarado's score was more accurate in males than in females. In this study, the average accuracy of the Alvarado score was: sensitivity 72.92%, specificity 67.17%, PPV 92%, NPV 35.8%, and DA 64.6%. in conclusion, the mean accuracy of the Alvarado score for diagnosing appendicitis cases in the Asian region shows that this score can still be used in daily practice. Accuracy of the diagnosis will increase if this scoring system is combined with USG or other biomarkers. Keywords: Alvarado score; accuracy; appendicitis Abstrak: Skor Alvarado merupakan sistem skor pertama yang dibentuk dan paling popular untuk mendiagnosis apendisitis, dengan klaim memiliki kelebihan yaitu akurasi diagnosis tinggi, sederhana dan efektif. Namun, dalam beberapa penelitian skor Alvarado dinilai kurang akurat dan bias terhadap ras, jenis kelamin, dan usia tertentu. Oleh karena itu, banyak bermunculan sistem skor baru dengan tujuan untuk menentukan diagnosis apendisitis yang lebih akurat. Penelitian ini bertujuan untuk mengetahui akurasi skor Alvarado pada kasus apendisitis. Jenis penelitian ialah suatu literature review menggunakan literatur pada Clinicalkey, Pubmed dan Google Cendekia dengan kriteria seleksi PICOS framework dan kata kunci 'accuracy' AND ‘alvarado score’ AND 'appendicitis' AND ‘Asia’ OR ‘Indonesia’ Hasil penelitian memperlihatkan tidak terdapat perbedaan akurasi skor yang bermakna dalam kelompok usia, akan tetapi skor Alvarado lebih akurat pada laki-laki dibandingkan perempuan. Pada studi ini didapatkan rerata akurasi dari skor Alvarado ialah: sensitivitas 72,92%; spesifisitas 67,17%; PPV 92%; NPV 35,8%; dan DA 64,6%. Simpulan penelitian ini ialah nilai rerata akurasi skor Alvarado untuk mendiagnosis kasus apendisitis di kawasan Asia menunjukkan bahwa skor ini masih dapat digunakan dalam praktik sehari-hari. Bila sistem skor ini dikombinasikan dengan pemeriksaan USG ataupun biomarker lainnya maka akurasi diagnosis akan meningkat. Kata kunci: skor Alvarado; akurasi; apendisitis